2013
DOI: 10.3892/or.2013.2343
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate promotes p53 accumulation and activity via the inhibition of MDM2-mediated p53 ubiquitination in human lung cancer cells

Abstract: Abstract. Epigallocatechin gallate (EGCG), which is derived from green tea, is well known for its chemopreventive activity. Several studies have shown that p53 plays an important role in the activity of EGCG; however, the mechanism by which EGCG regulates p53 requires further investigation. In the present study, we showed that EGCG inhibits anchorage-independent growth of human lung cancer cells by upregulating p53 expression. EGCG treatment can substantially increase p53 stability, promote nuclear localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…215 EGCG has been shown to block the interaction between mouse double minute 2 homolog (MDM2) and p53, thus inhibiting MDM2-mediated p53 ubiquitination, which directly affects DNA damage repair. 216 EGCG exhibits significantly greater anti-invasive properties than other catechins. EGCG reverses the epithelial-to-mesenchymal transition in melanoma cells.…”
Section: Importance Of Phytochemicals In Modulating the Functions Of mentioning
confidence: 99%
“…215 EGCG has been shown to block the interaction between mouse double minute 2 homolog (MDM2) and p53, thus inhibiting MDM2-mediated p53 ubiquitination, which directly affects DNA damage repair. 216 EGCG exhibits significantly greater anti-invasive properties than other catechins. EGCG reverses the epithelial-to-mesenchymal transition in melanoma cells.…”
Section: Importance Of Phytochemicals In Modulating the Functions Of mentioning
confidence: 99%
“…RNA extraction and RT-qPCR. RT-qPCR was performed as described previously (20). Total RNA was extracted from tissue specimens using TRIzol reagent (Invitrogen Life Technologies, Inc., Carlsbad, CA, USA) according to the manufacturer's instructions.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations and experimental studies have shown that green tea has chemopreventive effects for a wide range of malignancies, including lung, stomach, breast, prostate, pancreatic, ovarian, liver, colorectal and skin cancer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Mechanistic studies indicate that EGCG, the major component of green tea, appears to be the primary active ingredient responsible for its biological effects.…”
Section: Introductionmentioning
confidence: 99%